Development of ELISA test for the quality control of Pseudomonas aeruginosa recombinant vaccine based on the hybrid recombinant protein - A. V. Soldatenkova; A. M. Kudryashova; N. F. Gavrilova; I. V. Yakovleva; O. V. Borisova; V. V. Sviridov; N. A. Mikhailova (Медицинская иммунология)
A hybrid recombinant protein containing the amino  acid sequences of the three  most significant Pseudomonas aeruginosa antigens  (membrane proteins OprF, OprI  and toxoid  aTox)  was incorporated into a vaccine against Pseudomonas infection. Quality control of a hybrid recombinant protein and appropriate vaccine includes  determination of authentity and completeness of adsorption upon aluminum hydroxide adjuvant. The aim of our study was to develop  techniques of quality  control for a vaccine  based on the hybrid  OprF-aToxOprI  recombinant protein specific  to  P. aeruginosa.  Hybridomas secreting  specific  monoclonal antibodies for OprF-aTox-OprI were derived  from the fusion of myeloma cells and murine spleen  cells immunized with recombinant proteins P. aeruginosa. To  produce sufficient  quantities of antibodies, the  hybrid  cells were in vivo cultured in BALB/c mice.  Supernates and ascite liquids were chromatographically purified  with immune sorbent. Conjugation of antibodies with  horseradish peroxidase was carried  out  according to  P.K.Nakane. The  hybrid  OprF-aTox-OprI recombinant protein was detected by the  solid-phase ELISA, using a panel  of monoclonal antibodies and  conjugates of monoclonal antibodies with  horseradish peroxidase. Monoclonal antibodies were specific for different  OprF-aTox-OprI epitopes. Titration assays containing OprF-aTox-OprI protein at 78 ng/ml to 5000 ng/ml were used as quantitative standards for calibration curves.To identify  the recombinant protein OprF-aTox-OprI, 55 variants  of of MAb pairs were tested.  Limits  of quantitative detection served  for selection of most  sensitive  and  specific  ELISA  variants.  The  quantitative detection limit was calculated for all 11 ELISA  variants.  Two ELISA  variants  with the highest  sensitivity were selected  for  quality  control of the  hybrid  recombinant protein. The  limits  of quantitative detection were, respectively, 2.9 and 13.6 ng/ml (0.0058  and 0.027% of the estimated antigen  content in the vaccine)  for the first and  second  ELISA  variants.  The  first variant  included a pair  of monoclonal antibodies specific  for the OprF  and OprI  epitopes, the second  variant  represented aTox and OprI  epitopes. Two variants  of ELISA  were developed to detect  the hybrid recombinant OprF-aTox-OprI protein. The first variant allows to determine the protein amount and to evaluate completeness of its adsorption on aluminum hydroxide. To confirm authenticity of the protein, both methods must be used, since they can detect all three antigens (OprF, aTox and OprI) which are present  in the fusion protein.